2017
DOI: 10.1002/ijc.30616
|View full text |Cite
|
Sign up to set email alerts
|

Oncotype Dx recurrence score among BRCA1/2 germline mutation carriers with hormone receptors positive breast cancer

Abstract: Gene expression assays are widely used to predict risk of recurrence in early breast cancer (BC). We report the 21-gene expression assay (Oncotype Dx) recurrence score (RS) distribution of 27 BRCA carriers with estrogen receptor (ER) positive BCs, identified at Hadassah Medical Center, combined with 2 previous studies. Treatment decision and outcomes of the 27 BRCA carriers were compared with an Israeli cohort of 1594 patients published recently. We found Oncotype Dx RS low (<18), intermediate (18-30) and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 16 publications
1
14
0
1
Order By: Relevance
“…Other groups have demonstrated differences between BRCA2-associated HR-positive tumors versus sporadic HR-positive tumors, including in the distribution of Oncotype DX (Genomic Health) recurrence scores. [53][54][55] Because of the timeframe of primary tumor diagnoses encompassed in our study, we chose not to collect information on Oncotype Dx testing, nor did we perform tissue-based assays to identify other potential molecular differences that might also explain the differences in CNS relapse risk. Methodologic differences in BRCA1/BRCA2 mutation detection may cause some under ascertainment of carriers in this older cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Other groups have demonstrated differences between BRCA2-associated HR-positive tumors versus sporadic HR-positive tumors, including in the distribution of Oncotype DX (Genomic Health) recurrence scores. [53][54][55] Because of the timeframe of primary tumor diagnoses encompassed in our study, we chose not to collect information on Oncotype Dx testing, nor did we perform tissue-based assays to identify other potential molecular differences that might also explain the differences in CNS relapse risk. Methodologic differences in BRCA1/BRCA2 mutation detection may cause some under ascertainment of carriers in this older cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The RS is used to stratify early-stage hormone receptorepositive breast tumors into those with disease likely to respond to adjuvant cytotoxic chemotherapy. On the basis of existing cut points established by Genomic Health at the time of the study, RS was categorized into 3 risk groups: low (0-17), intermediate (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and high (! 31).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that patients with BRCA-associated breast cancers may have enhanced sensitivity to cytotoxic chemotherapy. [19][20][21][22] Although BRCA-associated tumors may have more aggressive features than sporadic breast cancers as a whole, more recent data suggest individuals with BRCA-associated breast cancers tend to have similar outcomes to those with sporadic cancers. 19,23e25 Additional studies of BRCA carriers have illustrated that they have a higher median RS, more high RS disease, more intermediate RS disease, and less low RS disease compared to sporadic breast cancer cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast cancer risk begins to rise at younger ages for BRCA1 mutation carriers compared with BRCA2 carriers . BRCA1 ‐mutant breast cancers are more often high grade, triple negative (TNBC) cancers (negative for estrogen receptor, progesterone receptor, and human epidermal growth factor receptor 2 [HER2]) and have a basal epithelial phenotype; whereas BRCA2 ‐mutant breast cancers more often exhibit a luminal B phenotype with expression of hormone receptors that have higher Oncotype Dx recurrence scores compared with sporadic tumors . The National Comprehensive Cancer Network guidelines recommend genetic testing for all patients aged ≤60 years who have TNBC, because 15% to 33% of these individuals will have an abnormal gene mutation …”
Section: Brca1/brca2 Mutations In Breast Cancermentioning
confidence: 99%